2005
DOI: 10.1093/carcin/bgi094
|View full text |Cite
|
Sign up to set email alerts
|

PKB/AKT and ERK regulation of caspase-mediated apoptosis by methylseleninic acid in LNCaP prostate cancer cells

Abstract: Methylselenol has been implicated as an active metabolite for the anticancer effect of selenium in part through the induction of cancer cell apoptosis. Since inactivation of the AKT/protein kinase B negative regulator gene PTEN (phosphatase and tensin homologue deleted on chromosome 10) is common in prostate cancer (PCa), we compared PTEN wild-type DU145 PCa cells (low basal AKT activity) with PTEN-mutant LNCaP PCa cells (high basal AKT activity) for their apoptosis responses to the methylselenol precursor met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
77
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 39 publications
10
77
1
1
Order By: Relevance
“…It is well established that HIF-1a is induced both by hypoxia and PI3K pathway in several cell types. 20,42,43 Even though several reports including ours 31,44 showed that selenium compounds could influence PI3K/Akt pathway in various cancer cell lines, this interaction has yet to be addressed under hypoxic conditions. DNA binding of HIF-1a is significantly reduced by MSeA in PAIII and PC-3 cells both in normoxia and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that HIF-1a is induced both by hypoxia and PI3K pathway in several cell types. 20,42,43 Even though several reports including ours 31,44 showed that selenium compounds could influence PI3K/Akt pathway in various cancer cell lines, this interaction has yet to be addressed under hypoxic conditions. DNA binding of HIF-1a is significantly reduced by MSeA in PAIII and PC-3 cells both in normoxia and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 A promising anticancer agent methylseleninic acid (MSeA) has been shown to be effective in inhibiting prostate cancer growth in vitro and in TRAMP model. 31,32 However, the potential of MSeA as a therapeutic agent has not been tested in humans, and the underlying mechanism(s) of selenium compounds including MSeA have not been studied in hypoxic conditions.…”
mentioning
confidence: 99%
“…[190][191][192] In vitro studies suggest that this effect may hinge to some degree on suppression of IκB kinase activation and NF-κB activity, as well as on an amplification of p53 function and a reduction in Akt phosphorylation. [193][194][195][196][197][198][199] This phenomenon may have important ramifications for chemotherapy/radiotherapy. Several years ago, Vadgama and colleagues reported that selenium potentiated the response of a range of human cancer cell lines to adriamycin or taxol in vitro.…”
Section: Multifocal Signal Modulation Therapies As Adjuvants To Cytotmentioning
confidence: 99%
“…In particular, an inorganic form of this compound, sodium selenite, was shown to increase the p38 and p53 phosphorylation, activating caspaseindependent cell death (11,12). Furthermore, this compound activates anti-apoptotic and the mitogen-activated protein inhibitor (MAPK) pathway to prevent damage to brain tissues and cells (13,14). However, few studies have been conducted to investigate whether selenium treatment and SelM overexpression affects the key regulator of AD pathology using a transgenic rat overexpressing the human SelM (hSelM) gene.…”
Section: Introductionmentioning
confidence: 99%